Post-COVID Syndrome in Children Residing in the Kabardino-Balkarian Republic - L. A. Temmoeva; Z. M. Alieva; Z. A. Kambachokova; N. M. Temmoev; D. A. Kardanova; D. S. Khozhaeva; A. L. Deshev; D. S. Malkarova; M. Kh. Dzhabrailova; A. T. Sheriev (Антибиотики и Химиотерапия, 2022)
A study which included 97 children who had COVID-19 during the period from September 2021 to January 2022 was conducted. This article discusses the symptoms occurring after COVID-19 infection. The analysis of the results showed that the largest proportion among sick children was in patients with reduced cognitive functions, an increased level of neuroticism, depressed state and emotional instability. The most common comorbidities were the diseases of the gastrointestinal tract, respiratory and cardiovascular systems.